Pengaruh Penerapan Sanksi Perpajakan Dan Pelayanan Pembayaran Pajak Kendaraan Bermotor Terhadap Kepatuhan Wajib Pajak Pada Kantor Samsat Kota Bengkulu - Jarkoni Jarkoni; Ayu Intan Oktaria (Jurnal Ekonomi dan Bisnis, 2023)
This research is motivated by a thought that with the existence of tax sanctions and good service to the community, it will increase taxpayer compliance. This study aims to determine how much influence the application of transportation sanctions and motor vehicle tax payment services has on taxpayer compliance at the Bengkulu City Samsat office. In this study, researchers used quantitative descriptive methods, data collection techniques using questionnaires and documentation. The data analysis technique used multiple linear regression test The results showed that the results of the t-test values (0.000 0.05) and (0.021 0.05). with an error rate of 5% while the f-test value showed a result of 21,529 and a probability of 0.000. And the results of the analysis of the correlation coefficient of 29.3%. Based on the results of the analysis, it can be concluded that the application of tax sanctions and motor vehicle tax payment services has an effect on taxpayer compliance at the Bengkulu City Samsat Office.